Volatile Organic Compounds (VOCs), Dihydroxyacetone (DHA) and Methylglyoxal (MGO) in Tropical Multifloral Honey (Apidae; Apis cerana) from sites of different geographical origin in Sabah, Borneo - Bellericter Binjamin; Mohd Iftar Johwan Johny-Hasbulah; Januarius Gobilik; Clament Chin Fui Seung; Lum Mok Sam; Nurul’azah Mohd Yaakub; Suzan Benedick (Researchgate, 2024)
The honey of stingless bees is considered a valuable commodity due to its therapeutic properties, but it is not known how the geographical areas in Sabah may affect the chemical composition of the honey. Therefore, the aim of this study was to determine the physicochemical properties, dihydroxyacetone (DHA) and methylglyoxal (MGO) content, and volatile organic compounds (VOCs) of Heterotrigona itama honey from three different geographical areas in Sabah: highland (10 samples), lowland (10 samples) and coastal (10 samples). The physicochemical parameters were assessed using established standard methods, DHA and MGO content were determined using high performance liquid chromatography (HPLC) and volatile organic compounds were identified using gas chromatography-mass spectrometry (GC-MS). The study concludes that the physicochemical properties, DHA and MGO content, and volatile organic compounds in the H. itama honey samples were strongly influenced by the geographical features in Sabah from which they were sourced. All H. itama honeys were below the maximum allowable levels for physicochemical parameters set by the Malaysian Standards (MS) for stingless bee honey. However, some parameters of the honeys exceeded the standards for physicochemical properties set by CODEX and USDA, indicating that the standards used for honeybees are not applicable in the quality classification of stingless bee honeys. The highland and lowland honeys had MGO with moderate antibacterial properties, the coastal honeys had MGO with low antibacterial properties, all of which are suitable for daily consumption. The highland honeys had the highest number of total and unique VOCs, followed by the coastal areas and the lowlands.